Service Quality of Public Preschool Education in Malaysia: Perceptions of Parents - Farah Laili Muda @ Ismail; Anita Ismail; Mohamad Aizuddin Abdul Aziz; Sumaiyah Abd Aziz; Nur Qamarina Sharom; Siti Rosilawati Ramlan (Universiti Sains Islam Malaysia, 2024)
The increasing number of preschools in Malaysia is a good sign of education development in the country. However, certain issues have risen up when each of the preschools offer different types of benefits such as curriculum, ambiance, quality of teachers and facilities that may lead to non-standardised quality of education. This study aims to explore the level of quality of public preschools in Malaysia from parents' perspectives. In Malaysia, there are four different government agencies providing the education that is (1) Jabatan Kemajuan Masyarakat or Community Development Department (local acronym is KEMAS) under Ministry of Rural and Regional Development, (2) Jabatan Perpaduan Negara or National Unity Department (local acronym is PERPADUAN) under the Ministry of National Unity and Social Integration, (3) Ministry of Education and (4) State Islamic Religion Department. Twelve parents who enrolled their children in public preschools were interviewed and the data were analyzed through content analysis. The result shows there are five main factors that constitute the quality of public preschool education in Malaysia, namely (1) school values, (2) school atmosphere, (3) health and wellbeing, (4) teachers and (5) facilities.